2007
DOI: 10.1002/er.1300
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic operation plan of a combined fuel cell cogeneration, solar module, and geo-thermal heat pump system using Genetic Algorithm

Abstract: A chromosome model that simulates the operation patterns of an energy system was introduced into a simple Genetic Algorithm, and a method of dynamic optimization was developed. This paper analyses the operation planning of an energy system that uses in combination a solar power module, proton-exchange membrane fuel cell cogeneration (PEMFC-CGS) with methanol steam reforming, a geo-thermal heat pump, heat storage and battery, commercial power, and a kerosene boiler. The hours of operation of each energy device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The system exergy efficiency is calculated with Eq. (11). It has been found that the exergy efficiency increment is not much between system 4 (quadrogeneration) and system 5 (five-product multigeneration).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The system exergy efficiency is calculated with Eq. (11). It has been found that the exergy efficiency increment is not much between system 4 (quadrogeneration) and system 5 (five-product multigeneration).…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, hybrid systems that are supplied by a combination of renewable sources can be justified for better effectiveness. Obara studied such a hybrid system supplied by geothermal and solar energy. In farming settings, apart from regular products (crops, vegetables, fruits, dairy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the reduction in losses is not up to mark; that is why proposed method is introduced so that problem of losses reduction can be more satisfactorily addressed. The demand response should be viewed as an energy tool that can be used in combination with DG and storage units to maintain the equilibrium of the process and optimize the operation of the power system 18‐24 . This article suggests a new peer‐to‐peer (P2P) local energy market architecture and probabilistic LMP for distribution systems central median price allocation and the P2P electricity exchange have each been mentioned as the viable alternatives to mainstream retail quality, strengthening the interaction with presumes share energy capital 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Obara 11 investigates a hybrid PVP/Fuel cell/Battery system, where fuel cell is another source besides the PVP.…”
Section: Introductionmentioning
confidence: 99%
“…In these hybrid systems, PVP and wind energy complement each other and the role of the battery is less important than in the PVP/Battery system. Similarly, Obara [11] investigates a hybrid PVP/Fuel cell/Battery system, where fuel cell is another source besides the PVP.…”
Section: Introductionmentioning
confidence: 99%